Scientific Argumentation in Chemistry Education: A Literature Review of Practices, Challenges, And Solutions - Putri, Tiara Swastika; Suyanta, Suyanta; Rohaeti, Eli (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study presents a systematic literature review (SLR) on students' scientific argumentation skills in chemistry education, focusing on practices, challenges, and potential solutions. Articles selected were sourced from the Scopus database using Publish or Perish (PoP) and published within the period of 2015-2024. Some of the notable issues identified in this review relate specifically to limited teacher preparation and low student engagement, which hinder the development of argumentation skills. Effective instructional models, strategies, and media that promote argument-driven learning are crucial according to these findings. Also, enhancing these specific skills requires targeted teacher training, curriculum integration of argumentative practices, and supportive classroom environments that cultivate inquiry-based learning and critical thinking. Generally, it sheds light on the importance of valid assessment tools to evaluate students' argumentation skills. Thus, strengthening these skills is essential for classroom members. Not only for acquiring a better understanding of chemical concepts but also for promoting scientific literacy as well as informed decision-making in broader societal contexts.